2022
DOI: 10.1371/journal.pmed.1004004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Growth Assessment Protocol (GAP) for antenatal detection of small for gestational age: The DESiGN cluster randomised trial

Abstract: Background Antenatal detection and management of small for gestational age (SGA) is a strategy to reduce stillbirth. Large observational studies provide conflicting results on the effect of the Growth Assessment Protocol (GAP) in relation to detection of SGA and reduction of stillbirth; to the best of our knowledge, there are no reported randomised control trials. Our aim was to determine if GAP improves antenatal detection of SGA compared to standard care. Methods and findings This was a pragmatic, superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…The consort diagram, characteristics of women included during the pre-randomisation and outcome comparison phases, and results of the analysis for primary and secondary clinical outcomes have been published previously. 6 Model parameter values estimated from the trial data based on the primary outcome definition of small babies identified at birth are described in Table 1; parentheses contain corresponding values based on the secondary definition of SGA. Cost-effectiveness results relating to the primary definition of SGA status are presented in Table 2 (results pertaining to the secondary definition in parentheses).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The consort diagram, characteristics of women included during the pre-randomisation and outcome comparison phases, and results of the analysis for primary and secondary clinical outcomes have been published previously. 6 Model parameter values estimated from the trial data based on the primary outcome definition of small babies identified at birth are described in Table 1; parentheses contain corresponding values based on the secondary definition of SGA. Cost-effectiveness results relating to the primary definition of SGA status are presented in Table 2 (results pertaining to the secondary definition in parentheses).…”
Section: Resultsmentioning
confidence: 99%
“…Five remaining cluster sites actually implemented GAP. 6 All women giving birth in a cluster site were included in the trial database. Women with multiple births, babies with congenital fetal anomalies and those born before 24 +1 gestational weeks were excluded from the analysis.…”
Section: Trial Design Population and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The DESiGN trial is the first and only randomised controlled trial comparing GAP to an alternative intervention. The clinical effectiveness trial found that GAP did not increase the rate of antenatal detection of SGA (the primary outcome), when compared to standard care [18]. This paper reports implementation outcome findings from the nested process evaluation and considers these in the light of the findings from the effectiveness study.…”
Section: Introductionmentioning
confidence: 95%
“…Strategies to improve the detection of abnormal fetal growth trajectories in the antenatal period have received deserved attention, and much effort has focused on the development of fetal growth centile charts. In an accompanying research study in PLOS Medicine , Vieira and colleagues assess customised growth charts devised as part of the Growth Assessment Protocol (GAP) against standard care across 13 hospitals in England, in the DESiGN cluster randomised trial [ 1 ].…”
mentioning
confidence: 99%